Orientasi Tafsir Ad-Durru Al-Mantsur fi Tafsir Al-Ma’tsur: Telaah Hadaf Tafsir dan Tsaqofah Al-Mufasirin - Raden Rifa Qodratinnisa; Reza Firmansyah; Eni Zulaiha (Jurnal Iman dan Spiritualitas, 2023)
This article intends to particularly explore the ittijah at-tafsir, also known as the orientation of interpretation, beginning with its definition, signs of emergence, and different types of orientation in interpretation. Through a survey of the literature, this research employs a qualitative method with an analytical-descriptive approach. This article will outline how to examine the Tsaqafah and As-motivation Suyuthi's for authoring Ad-Durru Al-Mantsur fi Tafsir Al-Ma'tsur in order to determine the orientation of the interpretation of the book. The Tsaqafah and hadaf of the mufasir are among the discussions that have a significant impact on how a book is interpreted. Conclusion: Personality features, academic prowess, one's environment, a mufasir's interests, and other factors are all interconnected with one's interpretation. As seen in the interpretation orientation of Ad-Durru Al-Mantsur fi Tafsir Al-Ma'tsur by As-Suyuthi.